Hak Korban Sebagai Dasar Pertimbangan Pemberian Pembebasan Bersyarat Kepada Narapidana Perkelahian dan Penganiayaan (Studi Kasus di Lembaga Pemasyarakatan Kelas IIA Pangkalpinang) - Briely Daffa Aufan; Faisal; Rio Armanda Agustian (Faculty of Law, University of Mataram, 2025)
Parole is a prisoner's right that includes four main conditions under Law Number 22 of 2022 concerning Corrections, without considering the rights of victims. The absence of consideration for victims' rights in the conditions for granting parole results in the violation of human rights for victims. This research discusses, first, the clash between victims' rights and prisoners' rights in granting parole to prisoners convicted of fighting and persecution at the Pangkalpinang Class IIA Penitentiary. Second, it examines the rights of victims as a basis for consideration in granting parole to prisoners convicted of fighting and persecution. The purpose of this study is to determine and analyze how the clash of rights and legal protection of victims is related to the granting of parole to prisoners convicted of fighting and persecution in Pangkalpinang City. The research employs an empirical juridical approach, using a statutory approach and data collection techniques through in-depth interviews with qualitative analysis. The results of this study reveal, first, a conflict between the rights of prisoners convicted of fighting and persecution to be granted parole and the human rights of victims due to the absence of consideration for victims' rights in granting parole under Law Number 22 of 2022 concerning Corrections. Preventive legal protection is carried out by the Correctional Institution in collaboration with the Correctional Center, supervised by the Directorate General of Corrections, to form a Community Research policy that listens to the opinions of victims in granting prisoners' rights and supervises to prevent prisoners from repeating criminal acts. Repressive legal protection is in the form of criminal sanctions and administrative sanctions. Second, the consideration of victims' rights in parole is not maximized, as it is only a secondary factor and does not significantly affect the granting of parole to prisoners convicted of fighting and persecution.